2018
DOI: 10.1097/rct.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment 18F-Fluorodeoxyglucose Positron Emission Tomography Standardized Uptake Values and Tumor Size in Medically Inoperable Nonsmall Cell Lung Cancer Is Prognostic of Overall 2-Year Survival After Stereotactic Body Radiation Therapy

Abstract: Both increased tumor size and metabolic activity are associated with increased risk of death. Combining size and metabolic activity together is superior for predicting 2-year survival and identifying patients for whom survival is statistically worse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Therefore, our study demonstrated stronger correlations between SUV values and PET/MRI than between those values and CT [29]. Tumor volume and SUV values are considered prognostic factors-increased values of both are associated with a higher risk of death [30,31]. Biologically, larger tumors have higher metabolic activity and therefore, higher SUV values indicate a worse prognosis [32].…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, our study demonstrated stronger correlations between SUV values and PET/MRI than between those values and CT [29]. Tumor volume and SUV values are considered prognostic factors-increased values of both are associated with a higher risk of death [30,31]. Biologically, larger tumors have higher metabolic activity and therefore, higher SUV values indicate a worse prognosis [32].…”
Section: Discussionmentioning
confidence: 53%
“…In addition to its value on clinical staging, at least some data suggest that it has role in predicting outcome [5, 6]. Tumor maximum standardized uptake value (SUV max ), a measure of cellular metabolic activity of the tumor, defined by PET-CT was reported to be an independent predictor of survival and relapse in early-stage NSCLC.…”
mentioning
confidence: 99%
“…Recently, some predictors have been reported to be associated with OS after SBRT, such as cardiac dose (Tembhekar et al 2017 ), mean lung dose (Dupic et al 2020 ), biologically effective dose (BED) of the prescription and maximum dose (Stahl et al 2016 ; Tateishi et al 2021 ), pre-treatment FDG-PET standardized uptake values (Kocher et al 2018 ), and pre-treatment hemoglobin level (Shaverdian et al 2016 ). Radiomics, a non-invasive technology that converts medical images into a high-dimensional mineable feature space via high-throughput quantitative feature extraction (Bera et al 2022 ; Gillies et al 2016 ; Lambin et al 2012 , 2017 ; Reuze et al 2018 ), has been introduced for the prediction of treatment responses, patient stratification, and prognosis for lung cancer patients in recent years (Chen et al 2017 , 2023 ; Constanzo et al 2017 ; Coroller et al 2015 ; Huang et al 2016 ; Lee et al 2017 ; Li et al 2018 ; Mattonen et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%